Implementasi Pendidikan Karakter Pancasila Di Madrasah Ibtidaiyah - Rahmayanti, Siti; Mariska, Firda; Cahya, Neelam; Ardani, Zidni Hilda; Fatimah, Siti; Fauziah, Muna (IAINU Kebumen, 2026)
This research is based on the importance of instilling and implementing Pancasila values to students in the current era of globalization in the field of education so that they understand Pancasila which is the basis of the Indonesian state. This study aims to provide a general description of the form of implementing Pancasila values in education at Madrasah Ibtidaiyah (MI) NURUL YAQIN in Pondokgebangsari, so that it can be used as reference material for readers, especially teachers and parties in the world of education, so that can implement this in the future. This research was written using a qualitative method of narrative research. In the technique of collecting data, this research is direct observation, interviews, questionnaire and documenting matters related to research. From the results of this study, it was obtained an overview of how the implementation of Pancasila values at MI NURUL YAQIN was through the learning process, religious amaliah activities, socio-cultural and extracurricular activities at the MI